SELECTION OF MARKER REGIONS OF GENES FOR THE MOLECULAR IDENTIFICATION OF HELMINTHS OF THE ASCARIDOIDEA SUPERFAMILY FOUND IN COD FISH - Jazina, K.T.; Uakhit , R.S.; Smagulova , A.M.; Valeyeva , D.M.; Manapov , N.S.; Lider , L.A.; Bulashev, A.K.; Kiyan, V.S. (Eurasian Journal of Applied Biotechnology, 2025)
In recent years, the consumption of imported fish has increased significantly in Kazakhstan, especially representatives of the cod family, which are characterized by a high level of parasitic invasion. Anisakidosis is a parasitic disease caused by nematodes of the Anisakidae family. The main symptoms of this disease are disorders of the gastrointestinal tract and allergic reactions. Humans are random hosts, consuming raw or undercooked fish and seafood. Until recently, it was believed that heat-treated fish was not dangerous, but recent studies show a high degree of allergy to anisakid antigens, which remain active after heat treatment. In addition, existing data indicate differences in the level of allergenicity between different species of nematodes in the family. In this regard, the species identification of anisakids is relevant for taxonomy, monitoring of distribution and minimizing potential risks to humans. Therefore, the purpose of this study is to select marker regions of genes for the identification of nematodes in cod family fish. Of the four types of primers, NC13/NC2 and NC5/NC2 are the most specific and optimal for amplifying the 5.8S and ITS-2 regions of rDNA. The nucleotide sequences obtained by us were identified as nematodes of the species Anisakis simplex and Hysterothylacium aduncum.